VIRUDDHA AHARA - THE UNIQUE CONCEPT OF AYURVEDA (International Journal of Ayurveda and Pharma Research, 2017)
Intake of food is one of the most essential activities for growth of the body and maintaining good health. Ancient Ayurveda texts explain a very unique concept of diet plans in the chapter known as Ahara vidhi - vidhan. Contradictory food is the sub-topic of this chapter. Ayurveda explains that, combination of certain incompatible food items in terms of taste, potencies, time, state of health, place, condition of Doshas, digestive fire, cooking methods, processing quantities, order of intake rules, is unsafe and that is called contradictory food (Viruddha ahara), that leads to obstruction of channels and produces acute and chronic diseases.Our ancient Ayurveda classics clearly defined this important concept and its types, and illustrated some examples and solutions. In todays modern era, due to lack of knowledge about correct eating habits, we blindly follow the wrong dietary habits and suffer from immunologic, skin allergic disorder and unknown etiology. By means of this article we can understand the disorders and hazardous effects of consumption of incompatible diets.Before consumption, one must consider whether the food combination is safe and is according to the rules and conditions for intake of food. However, it may be noted that for young and healthy person having good digestive capacity and regular exercising habits, consumption of contradictory diets in small quantities, may not pose serious risks. There is a serious need for research and deep study for analysis by expert dieticians and nutrition on contradictory diets for disseminating the facts and findings to the people for betterment of the society.